Changes in Student Learning Patterns Due to Dependence on Quick Search Technology - Sa'adah, Tanalina Lilatus; Al Qoyyim, Mutawalli Asya'rowi; Pambayun, Balqis Zurin Novara (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2025)
This article examines the significant shift in students' learning patterns caused by fast search technologies such as Google Search. The ease of accessing information has shifted learning from profound discovery to instant information retrieval, a phenomenon known as the "Google Effect" or Digital Amnesia, in which students tend to remember where information is found rather than the content itself. Although these technologies offer advantages such as speed, global accessibility, and quick problem-solving, excessive reliance on them can negatively affect concentration, synthesis skills, and critical reasoning. Therefore, educational systems must adapt by shifting assessment methods from memorization to analysis and source evaluation, while strengthening the curriculum to emphasize information literacy, algorithmic bias awareness, and source credibility verification. In this way, search technologies remain useful Research tools but should not replace deep thinking, allowing students to balance digital speed with intellectual depth..